Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1034/j.1601-5215.2002.51010.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Pressure Ulcer Prevention Guidelines: Implications for Nursing Home Quality

Abstract: NHs' overall adherence to PU prevention guidelines is relatively low and is characterized by large variations between homes in adherence to many recommendations. The low level of adherence and high level of variation to many best-care practices for PU prevention indicate a continued need for quality improvement, particularly for some guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 34 publications
3
34
1
4
Order By: Relevance
“…Low overall documentation of adherence to PU prevention protocols was already a concern in LTC facilities. 49 Previous studies using thigh monitoring of resident limb movements showed poor correlation of documentation with movement.…”
Section: Discussionmentioning
confidence: 99%
“…Low overall documentation of adherence to PU prevention protocols was already a concern in LTC facilities. 49 Previous studies using thigh monitoring of resident limb movements showed poor correlation of documentation with movement.…”
Section: Discussionmentioning
confidence: 99%
“…These could be lack of specific education on PU care, understaffed nursing teams, large number of patients, and lack of time and equipments. Saliba et al (2003) explored the application of PU prevention recommendations in 35 nursing homes in the United States. Disappointingly, the recommendations were followed only 41% of the time, with high variation existing between participating homes.…”
Section: Strategies For Pu Preventionmentioning
confidence: 99%
“…28 In the authors’ analyses for this study’s sample selection, they found that the performance variation continued. Taking advantage of this natural variation, the authors conducted semistructured interviews with staff from 6 CLCs representing a range of PrU prevention performance to identify contextual factors important in prevention.…”
Section: Discussionmentioning
confidence: 79%